Aerosol-Jet-Printed Encapsulation of Organic Photovoltaics - Basu, Robin; Siah, Kok Siong; Distler, Andreas; Häußler, Felix; Franke, Jörg; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Engineering Materials, 2023)
Organic electronic devices (OEDs) are prone to oxygen- and water-induced degradation and therefore need to be encapsulated with barrier materials. In this work, an aerosol jet (AJ)-printing process is developed to coat perhydropolysilazane (PHPS) directly onto OEDs by adapting the print setup and systematically optimizing the process parameters. Furthermore, a novel curing process that converts PHPS to silica barrier layers is developed by combining damp heat (DH) exposure with subsequent vacuum–UV irradiation. This two-step treatment is shown to be considerably faster and gentler than the state-of-the-art curing processes and also yields a quantitatively higher conversion. Both the printing and the conversion process are fully compatible with OED devices, which is demonstrated by a damage-free direct encapsulation of organic solar cells. The encapsulated cells show a significant reduction of degradation in DH conditions (65 °C/85% r.h.), maintaining >95% of their initial performance for >100 h. Complementary electroluminescence measurements reveal that the AJ-printed barrier layers effectively prevent lateral water ingress into the devices. Herein, the proof of principle is provided that AJ printing can be used to print barrier layers directly onto OEDs and is thus an industrially highly relevant technology to precisely encapsulate such devices even on 3D objects.
CRIS-Team Scopus Importer:2023-07-07
Keywords: aerosol jet printing; organic solar cells; perhydropolysilazane; printed barriers; solution-processed encapsulation

A generic surfactant-free approach to overcome wetting limitations and its application to improve inkjet-printed P3HT:non-fullerene acceptor PV - Maisch, Philipp; Eisenhofer, Lena M.; Tam, Kai Cheong; Distler, Andreas; Voigt, Monika M.; Brabec, Christoph; Egelhaaf, Hans-Joachim (Journal of Materials Chemistry A, 2019)
Solution based thin film technology often implies challenging wetting behaviour which has to be improved in order to achieve good printing or coating qualities. A common way of solving such problems is the use of wetting agents but they often show undesired side effects. In this work, we introduce a generic strategy to overcome this problem. We demonstrate inkjet printed arrays of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) dots to efficiently pin the three-phase contact line of wet films, thereby enforcing homogenous wetting and subsequent drying on low energetic surfaces. By printing and drying single droplets of ink, a matrix of anchoring points is created which pins the subsequently printed continuous wet layer and thus enables the coating of large surface areas with homogeneous, defect free films. This method also allows convenient patterning of surfaces by combining inkjet-printing of anchoring points with subsequent large area flood coating, e.g., by doctor blading. Furthermore, the defined placement of each anchoring point allows full thermodynamic control of the film formation by quantitative calculation of the processing windows and patterning precision. The beneficial application of this new strategy to printed electronics is demonstrated by fabricating organic solar cells with power conversion efficiencies of 5%. This is achieved by printing a hydrophilic PEDOT:PSS electron blocking layer without addition of surfactants at unprecedented quality onto an otherwise non-wettable hydrophobic active layer consisting of poly(3-hexylthiophene) (P3HT) and the indacenodithiophene-based non-fullerene acceptor O-IDTBR.
CRIS-Team Scopus Importer:2019-06-18

A High Throughput Platform to Minimize Voltage and Fill Factor Losses - Haffner-Schirmer, Julian; Le Corre, Vincent Marc; Forberich, Karen; Egelhaaf, Hans-Joachim; Osterrieder, Tobias; Wortmann, Jonas; Liu, Chao; Weitz, Paul; Heumüller, Thomas; Bornschlegl, Andreas; Wachsmuth, Josua; Distler, Andreas; et al. (Advanced Energy Materials, 2025)
Organic photovoltaics (OPV) now can exceed 20% power conversion efficiency in single junction solar cells. To close the remaining gap to competing technologies, both fill factor and open-circuit voltage must be optimized. The Langevin reduction factor is a well-known concept that measures the degree to which charge extraction is favored over charge recombination. It is therefore ideally suited as an optimization target in high-throughput workflows; however, its evaluation so far requires expert interaction. Here, an integrated high-throughput workflow is presented, able to obtain the Langevin reduction factor within a few seconds with high accuracy without human intervention and thus suited for autonomous experiments. This is achieved by combining evidence from UV–vis spectra, current–voltage curves, and a novel implementation of microsecond transient absorption kinetics allowing, for the first time, the intrinsic determination of charge absorption cross-sections, which is crucial to reporting stationary charge densities. The method is demonstrated by varying the donor:acceptor ratio of the high performance OPV blend PM6:Y12. The high reproducibility of the method allows to find a strictly exponential relationship between the PM6 exciton energy and the Langevin reduction factor.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge dynamics; high throughput; Langevin reduction factor; organic photovoltaics; transient absorption kinetics

All inkjet-printed organic solar cells on 3D objects - Steinberger, Marc; Distler, Andreas; Hörber, Johannes; Tam, Kai Cheong; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2024)
Drop-on-demand inkjet printing is a promising and commercially relevant technology for producing organic electronic devices of arbitrary shape on a wide variety of different substrates. In this work we transfer the inkjet printing process of organic photovoltaic devices from 2D to 3D substrates, using a 5-axis robot system equipped with a multi-nozzle inkjet printing unit. We present a ready-to-use 3D printing system for industrial application, using a 5-axis motion system controlled by commercial 3D motion software, combined with a commonly used multi-nozzle inkjet print head controlled by the corresponding printing software. The very first time inkjet-printed solar cells on glass/ITO with power conversion efficiencies (PCEs) of up to 7% are realized on a 3D object with surfaces tilted by angles of up to 60° against the horizontal direction. Undesired ink flow during deposition of the inkjet-printed layers was avoided by proper ink formulation. In order to be able to print organic (opto-)electronic devices also on substrates without sputtered indium tin oxide bottom electrode, the bottom electrode was inkjet-printed from silver nanoparticle (AgNP) ink, resulting in the first all inkjet-printed (i.e. including bottom electrode) solar cell on a 3D object ever with a record PCE of 2.5%. This work paves the way for functionalizing even complex objects, such as cars, mobile phones, or ‘Internet of Things’ applications with inkjet-printed (opto-)electronic devices.
CRIS-Team Scopus Importer:2024-07-05
Keywords: 3D functionalization; 3D printing; inkjet printing; organic solar cells; silver nanoparticles

All sub-nanosecond laser monolithic interconnection of OPV modules - Kubis, Peter; Winter, Jan; Gavrilova, Anna; Hennel, Markus; Schlosser, Susanne; Richter, Isabel; Distler, Andreas; Heyder, Madeleine; Kery, Stefan; Lenk, Peter; Geiger, Stephan; Brabec, Christoph; et al. (Progress in Photovoltaics, 2019)
Although green femtosecond lasers provide outstanding quality and wide processing windows for monolithic interconnection of the individual cells in organic photovoltaic (OPV) modules, they are hardly used in commercial applications, due to cost reasons. In this work, a process has been developed that allows the monolithic interconnection in OPV modules with an infrared sub‐nanosecond laser exclusively, without compromising the performance of the modules. While the photoactive layer is removed easily by green femtosecond pulses without damaging the bottom electrode, this is not possible for infrared nanosecond pulses, due to their much larger optical penetration length, which significantly exceeds the thickness of the active layer and is well absorbed by the indium tin oxide (ITO) layer. This leads to damage of the ITO bottom electrode, which in turn compromises the functionality of the module. By systematically varying single‐pulse laser fluence and spatial pulse overlap, the laser parameters are optimized in such a way that the contact area between the residues of the metal oxide bottom electrode and the silver nanowire top electrode is maximized so that the electrical resistances of the contacts are sufficiently small not to affect device performance. This is demonstrated by presenting large‐area OPV modules based on the well‐characterized reference system P3HT:PCBM that show efficiencies of up to 2.4%. This achievement opens up the way towards reliable roll‐to‐roll (R2R) laser patterning processes with sub‐nanosecond lasers and thus represents a breakthrough with respect to cost‐effective R2R manufacturing of OPV modules, due to grossly reduced investment and maintenance costs for laser sources.<br
Keywords: sub-nanosecond pulses; flexible organic photovoltaic module; laser patterning

Analyzing the outdoor degradation behavior of organic solar modules in North China - Liu, Shaopeng; Zhang, Dawei; Egelhaaf, Hans-Joachim; Wang, Gaoyuan; Li, Xiaogang; Heumüller, Thomas; Brabec, Christoph; Li, Ning (Journal of Materials Chemistry A, 2024)
The outdoor stability of organic solar modules (OSMs) directly determines the success of the organic photovoltaic (OPV) technology, which is critically important but insufficiently studied so far. Here, we perform a systematic study on the long-term outdoor exposure of OSMs according to the ISOS-O-2 standard lasting over two years. OSMs featuring a large active area (108 cm2), lightweight design (∼22 g), and typical PCE value (4.2%) were utilized in this study. The environmental data and OSMs' property data are synchronously collected to investigate the relationship between the outdoor properties of OSMs and environmental factors with the aid of machine learning and traditional mathematical methods. Based on the experimental results, we quantify the OSMs' degradation process and evaluate the long-term stability of OSMs. Encouragingly, we find that the long-term operational stability of OSMs is quite impressive under the outdoor aging conditions in North China. The initial outdoor PCE value was around 4%, maintaining over 3.3% even after two years of outdoor exposure. The extrapolated degradation rate remained below 2% per year, despite the burn-in process. The observed burn-in process during outdoor degradation suggests that mitigating burn-in loss could enhance the field stability of OSMs, and that the outdoor environment can be effectively simulated in a well-designed laboratory setting for stability studies. All of this suggests a bright future for further development of OPV technology towards commercialization and practical outdoor applications.
CRIS-Team Scopus Importer:2024-05-31

A phase-field model for the evaporation of thin film mixtures - Ronsin, Olivier; Jang, Dongju; Egelhaaf, Hans-Joachim; Brabec, Christoph; Harting, Jens (Physical Chemistry Chemical Physics, 2020)

Challenges and opportunities in upscaling inkjet-printing of OPV - Steinberger, Marc; Qingguang, Xie; Ronsin, Olivier J.J.; Maisch, Philipp; Tam, Kai Cheong; Distler, Andreas; Harting, Jens; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2024)
The power conversion efficiency and long-term stability of organic solar cells have increased tremendously over the past years, reaching up to 19.2% on research cells and 14.5% on large modules. To take the final step towards industrialization, fabrication methods that can be upscaled and directly implemented in industrial processes need to be developed. In recent years, well-known industrial techniques, like drop-on-demand inkjet printing, have been further developed within the organic photovoltaics (OPV) community, as it enables versatile printing of arbitrary, free-form organic solar modules with different colors-a key feature for modern building-integrated photovoltaics and several niche applications of OPV printed on any kind object. In this review, aside a brief summary of recent developments, we provide an overview of the biggest challenges in OPV inkjet-printing and define design rules to overcome these issues. Further perspectives of OPV inkjet-printing conclude the review.
CRIS-Team Scopus Importer:2025-02-04
Keywords: inkjet-printing; organic photovoltaics; upscaling

CO2 snow jet cleaning as a roll-to-roll compatible method for deburring IMI substrates after laser patterning - Wagner, Michael; Distler, Andreas; Schmidt, Hans-Dieter; Classen, A.; Stubhan, T.; Koegl, M.; Illg, J.; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2023)
Burring is commonly encountered upon patterning of dielectric-metal-dielectric (DMD) transparent electrodes by laser ablation. These burrs are conductive and thus lead to shunting of the (opto-)electronic devices built upon these electrodes. In this work, CO2 snow jet blasting is presented as a convenient and reliable method for deburring laser-patterned DMD electrodes during roll-to-roll manufacturing of organic solar modules. As CO2 snow jet blasting significantly reduces the extent of shunting and concomitantly avoids scratching the electrode, the photoelectrical conversion efficiencies of the solar modules thus produced are higher than those obtained for traditional deburring techniques.
CRIS-Team Scopus Importer:2023-02-10
Keywords: carbon dioxide snow jet; deburring; laser patterning; printed photovoltaics; transparent electrode

Comparative analysis of outdoor energy harvest of organic and silicon solar modules for applications in BIPV systems - Feroze, Sarmad; Distler, Andreas; Forberich, Karen; Ahmed Channa, Iftikhar; Doll, Bernd; Brabec, Christoph; Egelhaaf, Hans-Joachim (Solar Energy, 2023)
Organic photovoltaics (OPV) have the potential to fill niches that traditional silicon photovoltaics (Si-PV) have left open so far. Building-integrated photovoltaics (BIPV) is one key area where OPV modules can play a vital role due to their functional attributes of semitransparency, flexibility, and lightweight. However, the architectural constraints and physical layout of buildings often do not allow the installation of photovoltaic (PV) modules at their optimal angles. Herein, we report the outdoor energy harvest of commercial OPV, and monocrystalline silicon (m-Si) modules mounted at inclinations of 45° and 90°, using the ISOS-O2 protocol as a test standard. The semitransparent OPV modules incorporating a P3HT:PCBM bulk heterojunction absorbing layer were found to offer daily specific energy yields (YF) that are 10–15% higher than those of the m-Si modules at 45° inclination. For vertical (90°) mounting, the YF of the OPV modules is even 24–30% higher than that of their inorganic counterparts, thus making them ideally suited for façade integrated BIPV. Laboratory investigations reveal that the superior performance of OPV modules in the vertical position is mainly due to a strongly enhanced fill factor (FF) at reduced in-plane irradiance. At a 45° inclination, the positive temperature coefficient of the OPV modules also plays an important role during high-irradiance hours.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Building-integrated photovoltaics; Energy harvest; Organic photovoltaics; Outdoor monitoring

Cutting “lab-to-fab” short: high throughput optimization and process assessment in roll-to-roll slot die coating of printed photovoltaics - Wagner, Michael; Distler, Andreas; Le Corre, Vincent Marc; Zapf, Simon; Baydar, Burak; Schmidt, Hans-Dieter; Heyder, Madeleine; Forberich, Karen; Lüer, Larry; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2023)
Commercialization of printed photovoltaics requires knowledge of the optimal composition and microstructure of the single layers, and the ability to control these properties over large areas under industrial conditions. While microstructure optimization can be readily achieved by lab scale methods, the transfer from laboratory scale to a pilot production line (“lab to fab”) is a slow and cumbersome process: first, the difficulty of operating structure-sensitive methods in-line impedes proper microstructure characterization, and second, the processing-functionality relationship must be redetermined for every material combination as the results obtained by typical lab-scale spin-coating cannot be directly transferred to other coating methods. Here, we show how we can optimize the performance of organic solar cells and at the same time assess process performance in a 2D combinatorial approach directly on an industrially relevant slot die coating line. This is enabled by a multi-nozzle slot die coating head allowing parameter variations along and across the web. This modification allows us to generate and analyze 3750 devices in a single coating run, varying the active layer donor : acceptor ratio and the thickness of the electron transport layer (ETL). We use Gaussian Process Regression (GPR) to exploit the whole dataset for precise determination of the optimal parameter combination. Performance-relevant features of the active layer morphology are inferred from UV-Vis absorption spectra. By mapping morphology in this way, small undesired gradients of process conditions (extrusion rates, annealing temperatures) are detected and their effect on device performance is quantified. The correlation between process parameters, morphology and performance obtained by GPR provides hints to the underlying physics, which are finally quantified by automated high-throughput drift-diffusion simulations. This leads to the conclusion that voltage losses which are observed for very thin ETL coatings are due to incomplete coverage of the electrode by the ETL, which causes enhanced surface recombination.
CRIS-Team Scopus Importer:2023-11-10

Design of Highly Efficient Semitransparent Perovskite/Organic Tandem Solar Cells - Rossi, Daniele; Forberich, Karen; Matteocci, Fabio; Der Maur, Matthias Auf; Egelhaaf, Hans-Joachim; Brabec, Christoph; Di Carlo, Aldo (Solar RRL, 2022)
Solar cells transparent in the visible range are highly requested for integration in see-through photovoltaic (PV) applications such as building glass façades or greenhouse roofs. The development of advanced transparent PV can fully exploit the tandem technology where the top cell absorbs the near-ultraviolet solar spectrum while the bottom one absorbs the near-infrared part. Herein, a possible implementation of this tandem PV paradigm, namely, the tandem structure composed of a high-bandgap halide perovskite solar cell and a low-bandgap organic solar cell, is considered. Electro-optical simulation results based on parameters calibrated on experimental data show that an efficiency of 15% can be achieved with an average visible transmittance above 50%. This can be obtained considering the halide perovskite with mixed chlorine and bromine anions, a nonfullerene-based bulk heterojunction, a well-calibrated light management, and a three-terminal configuration of the tandem.
CRIS-Team Scopus Importer:2022-07-08
Keywords: organic solar cells; pervoskite solar cells; solar cell simulations; tandem perovskite/organic solar cells; transparent solar cells

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, Dongju; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Fassadenelemente mit organischer Photovoltaik - Egelhaaf, Hans-Joachim; Brabec, Christoph; Neberich, Marcel; Senguttuvan, Kaushik; Hoga, Felix; Kießling, Günther; Braun, Matthias; Bordin, Susanna; Wagner, Michael; Distler, Andreas; Feroze, Sarmad; Dentel, Arno (BWK Das Energie Fachmagazin, 2021)
In dem vom Bundesministerium für Wirtschaft und Energie (BMWi) geförderten Projekt „Fassade3“ entwickelt ein Konsortium aus akademischen und industriellen Partnern ein multifunktionales Fassadenelement mit integrierter organischer Photovoltaik (OPV). Die Fassade kann aufgrund ihrer modularen Struktur vorgefertigt und sowohl in Neu- als auch Bestandsgebäude integriert werden. Sie fungiert als Energiequelle, dient der thermischen Isolation, bietet Sonnenschutz für den Innenraum und optimiert so die Energieeffizienz des Gebäudes. Mit einfachen Mitteln lässt sich somit eine voll funktionsfähige und gleichzeitig ästhetisch ansprechende Konstruktion realisieren. Ein eigens entwickeltes Messsystem erlaubt die Echtzeit-Überwachung der Energiebilanz der Fassade. Erste Ergebnisse zum Leistungsverhältnis der OPV-Module sind vielversprechend.

Fully Printed and Industrially Scalable Semitransparent Organic Photovoltaic Modules: Navigating through Material and Processing Constraints - Wachsmuth, Josua; Distler, Andreas; Liu, Chao; Heumüller, Thomas; Liu, Yang; Aitchison, Catherine M.; Hauser, Alina; Rossier, Michael; Robitaille, Amélie; Llobel, Marc Antoine; Morin, Pierre Olivier; Thepaut, Anaïs; et al. (Solar RRL, 2023)
While the power conversion efficiency (PCE) of organic photovoltaics (OPV) on small-area lab cells has rapidly increased during the last few years, the performance on module level and the availability of OPV modules on the market is still limited, primarily due to specific constraints imposed by the industrial production process. This work deals with the upscaling process of latest-generation OPV from small-area lab cells to fully solution-processed modules, which are compatible to industrial roll-to-roll (R2R) printing. This transfer is demonstrated step by step from material selection and process optimization for every single layer of the stack (photoactive layer, charge transporting layers, and solution-processed top electrode)–including long-term stability investigations (thermal and light)–to scaling up the device area by a factor of >100. Thus, a semitransparent OPV module with 10.8% PCE on 10.2 cm2 active area is achieved, which is among the highest performances for semitransparent, fully solution-processed OPV modules. The individual developments all meet the requirements for industrial R2R printing (green solvents, processing in air, annealing ≤140 °C, etc.), which ensures that both the optimized layer stack and the fabrication process are fully scalable and easily transferable to large-scale production.
CRIS-Team Scopus Importer:2023-09-22
Keywords: ambient air; organic photovoltaics (OPVs); roll-to-roll (R2R)-compatibility; semitransparent modules; solution-processing; upscaling

Fully printed flexible perovskite solar modules with improved energy alignment by tin oxide surface modification - Dong, Lirong; Qiu, Shudi; García Cerrillo, José; Wagner, Michael; Kasian, Olga; Feroze, Sarmad; Jang, Dongju; Li, Chaohui; Le Corre, Vincent Marc; Zhang, Kaicheng; Peisert, Heiko; U. Kosasih, Felix; et al. (Energy and Environmental Science, 2024)
Fully printed flexible perovskite solar cells (f-PSCs) show great potential for the commercialization of perovskite photovoltaics owing to their compatibility with high-throughput roll-to-roll (R2R) production. However, the challenge remains in the deficiency in controlling interfacial recombination losses of the functional layer, causing remarkable loss of power conversion efficiency (PCE) in industrial production. Here, a fullerene-substituted alkylphosphonic acid dipole layer is introduced between the R2R-printed tin oxide electron transport layer and the perovskite active layer to reduce the energetic barrier and to suppress surface recombination at the buried interface. The resulting f-PSCs exhibit a PCE of 17.0% with negligible hysteresis, retain 95% of their initial PCE over 3000 bending cycles and achieve a T95 lifetime of 1200 h under 1 sun and 65 °C in nitrogen atmosphere. Moreover, the fully printed flexible perovskite solar mini-modules (f-PSMs) with a 20.25 cm2 aperture area achieve a PCE of 11.6%. The encapsulated f-PSMs retain 90% of their initial PCE after 500 h damp-heat testing at 65 °C and 85% relative humidity (ISOS-D3). This work marks an important progress toward the realization of efficient and stable flexible perovskite photovoltaics for commercialization.
CRIS-Team Scopus Importer:2024-08-16

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands - Yousefiamin, Amirabbas; Killilea, Niall Andrew; Sytnyk, Mykhailo; Maisch, Philipp; Tam, Kwok-Kan; Egelhaaf, Hans-Joachim; Langner, Stefan; Stubhan, Tobias; Brabec, Christoph; Rejek, Tobias; Halik, Marcus; Poulsen, Katharina; et al. (ACS nano, 2019)
Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (similar to 10(12) cm Hz(1/2) /W) and a cut-off frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabilized by perovskite-like methylammonium iodobismuthate ligands, which are dispersed in a ternary solvent. Fully inkjet printed devices based on this solvent were achieved with printed silver electrodes and a ZnO interlayer. Considerable improvements were obtained by the addition of small amounts of the polymer poly(vinylpyrrolidone) to the ink. The polymer improved the colloidal stability of the ink and its film-formation properties and thus enabled the scalable printing of single detectors and detector arrays. While photoconductors were shown here, the developed ink will certainly find application in a series of further electronic devices based on nanocrystals from a broad range of materials.
Keywords: colloidal nanocrystals; infrared detectors; inkjet printing; PbS; solution processing

Fully printed organic solar modules with bottom and top silver nanowire electrodes - Tam, Kai Cheong; Kubis, Peter; Maisch, Philipp; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2021)
One of the advantages of organic photovoltaics (OPV) over other contemporary technologies is its relative ease of processing. There are, however, very few works that have realized fully printed devices, including the bottom electrode, let alone with a scalable process in a reasonable device size (>1 cm(2)). In this work, design steps and optimization processes towards fully printed OPV modules with scalable processes are demonstrated for the first time. An overview on issues related to upscaling with printed electrodes is first provided. The various issues are then addressed by a rational design process supported by measurements and calculations. Finally, a set of fully printed OPV modules are fabricated using these optimized parameters that have over 3.5-cm(2) active area with 5% efficiency. For the first time, this work has also demonstrated the process compatibility of fully printed device structures with non-fullerene acceptor systems, which enables more design opportunities for the current generation of high-performance OPV materials.
CRIS-Team WoS Importer:2021-12-31

Fully solution-processed, light-weight, and ultraflexible organic solar cells - Güler, Ezgi; Distler, Andreas; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2022)
Organic photovoltaic (OPV) devices have the potential to be superior to other PV technologies for the use in applications that require very high flexibility or maximum specific power (power-per-weight ratio), such as textile integration, wearable electronics, or outer space applications. However, OPV devices also require encapsulation by barrier films to reduce the degradation driven by extrinsic factors, which in turn limits their flexibility and leads to lower specific power values. In this work, fully solution-processed (including both electrodes) semitransparent organic solar cells (OSCs) with performance comparable with conventional indium tin oxide-based devices are processed directly onto different barrier films of varying thicknesses. Direct cell fabrication onto barrier films leads to the elimination of the additional polyethylene terephthalate substrate and one of the two adhesive layers in the final stack of an encapsulated OPV device by replacing the industrial state-of-the-art sandwich encapsulation with a top-only encapsulation process, which yields significantly thinner and lighter 'product-relevant' PV devices. In addition to the increase of the specific power to 0.38 W g(-1), which is more than four times higher than sandwich-encapsulated devices, these novel OSCs exhibit better flexibility and survive 5000 bending cycles with 4.5 mm bending radius. Moreover, the devices show comparable stability as conventionally encapsulated devices under constant illumination (1 sun) in ambient air for 1000 h. Finally, degradation under damp heat conditions (65 degrees C, 85% rh) was investigated and found to be determined by a combination of different factors, namely (UV) light soaking, intrinsic barrier properties, and potential damaging of the barriers during (laser) processing.
CRIS-Team WoS Importer:2022-05-13
Keywords: solution-processability; specific power; organic photovoltaics; silver nanowire; transparent electrodes; flexible electronics; barrier films

Fully Solution Processed Pure α-Phase Formamidinium Lead Iodide Perovskite Solar Cells for Scalable Production in Ambient Condition - Yang, Fu; Dong, Lirong; Jang, Dongju; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Guo, Fei; Li, Cong; Arrive, Charline; Bertrand, Mélanie; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2020)
Manufacturing commercially viable perovskite solar cells still requires appropriate low-temperature and scalable deposition processes to be developed. While α-phase FAPbI3 has higher thermal stability and broader absorption than MAPbI3, there still is no report of a pure α-phase FAPbI3 perovskite film obtained by a scalable printing method. Moreover, spontaneous conversion of the α-phase to non-perovskite δ-phase under ambient conditions poses a serious challenge for practical applications. Herein, a scalable and fully solution based printing method for the fabrication of pure α-phase FAPbI3 perovskite solar cells is reported. Through adding N-methyl pyrrolidone and methylammonium chloride to the dimethylformamide based precursor solution to control the crystallization, and vacuum or air-flow assisted film drying, pure α-FAPbI3 phase is obtained by doctor blading. The resulting α-FAPbI3 film is highly stable, with no δ-FAPbI3 phase being formed even after keeping it in an ambient atmosphere over a period of 200 days without encapsulation. In addition, a fully solution processed PSC with a PCE of 16.1% is processed by the vacuum assisted method, and 17.8% by the air-flow assisted method. Replacing silver with a printed carbon electrode provides a stable PCE up to 15% for the vacuum assisted and 16.4% for the air-flow assisted method, which is the highest performance of FAPbI3 solar cells to date. Compared with MAPbI3, the fully printed FAPbI3 perovskite devices exhibit a remarkable thermal stability in humid atmospheres which makes them a promising candidate for scalable production and commercialization.
CRIS-Team Scopus Importer:2020-10-02
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; α-FAPbI

Increased thermal stabilization of polymer photovoltaic cells with oligomeric PCBM - Ramanitra, Hasina H.; Dowland, Simon A.; Bregadiolli, Bruna A.; Salvador, Michael; Silva, Hugo Santos; Begue, Didier; Graeff, Carlos F. O.; Peisert, Heiko; Chasse, Thomas; Rajoelson, Sambatra; Osvet, Andres; Brabec, Christoph; et al. (Journal of Materials Chemistry C, 2016)
The first oligomerisation of phenyl-C-butyric acid methyl ester (PCBM) using a facile atom transfer radical addition polymerization (ATRAP) and its exploitation for organic photovoltaic devices is described. Oligo(phenyl-C-butyric acid methyl ester)-alt-[1,4-bis(bromomethyl)-2,5-bis(octyloxy)benzene] (OPCBMMB) shows opto-electronic properties equivalent to those of PCBM but has a higher glass transition temperature. When mixed with various band gap semiconducting polymers, OPCBMMB delivers performances similar to PCBM but with an enhanced stabilization of the bulk heterojunction in photovoltaic devices on plastic substrates under thermal stress, regardless of the degree of crystallinity of the polymer and without changing opto-electronic propertie
Keywords: Engineering controlled terms: Atom transfer radical polymerization; Electronic properties; Energy gap; Esters; Free radical reactions; Glass transition; Heterojunctions; Oligomers; Photoelectrochemical cells; Photovoltaic cells; Semiconducting polymers; Stabilization; Substrates Atom transfer radical addition; Bulk heterojunction; Degree of crystallinity; Optoelectronic properties; Organic photovoltaic devices; Photovoltaic devices; Polymer photovoltaic cells; Thermal stabilization Engineering main heading: Butyric acid

Infrared Absorption Imaging of Water Ingress Into the Encapsulation of (Opto-)Electronic Devices - Hepp, Johannes; Vetter, Andreas; Langner, Stefan; Woiton, Michael; Jovicic, Gordana; Burlafinger, Klaus; Hauch, Jens; Camus, Christian; Egelhaaf, Hans-Joachim; Brabec, Christoph (IEEE Journal of Photovoltaics, 2019)
Water ingress into the encapsulation of electronic devices is a serious issue, especially for organic and perovskite-based electronics. In order to guide the development of suitable barrier materials and design, a reliable, fast, and non-destructive analysis tool is required. In this work, an imaging setup is presented, which is based on selective infrared (IR) radiation sources and a mid-IR sensitive camera that uses the absorption hand of water around 1920 nm and a reference band. This system enables us to monitor the distribution of water concentration inside the packaging of devices and its change over time. Our measurement is capable of detecting the local presence of water down to the mg/m(2) concentration range in a wide variety of encapsulation materials. The new tool allows identifying the pathways of moisture ingress into the encapsulation along with the corresponding diffusion coefficient. Thus, it provides fast and reliable analysis of humidity related failure mechanisms, and consequently helps to improve the design of encapsulation materials and processes.
Keywords: Degradation; diffusion processes; optical signal detection; organic photovoltaics (PVs); packaging

Inkjet printed organic and perovskite photovoltaics—review and perspectives - Maisch, Philipp; Tam, Kai Cheong; Jang, DongJu; Steinberger, Marc; Yang, Fu; Brabec, Christoph; Egelhaaf, Hans-Joachim (Organic Flexible Electronics, 2021)
This chapter provides a review on digital printing of organic solar cells (OSCs) and perovskite solar cells (PSCs). It starts with a brief introduction to the fundamentals of both solar technologies. Highlighting the specific demands of many novel solar applications, the necessity to fabricate devices using cheap and most versatile techniques, such as drop-on-demand inkjet, is outlined. A short discussion on the fundamentals of inkjet technology provides the background for a literature overview on digitally printed OSCs and PSCs. The main part of this chapter describes the most significant achievements in the field and remaining challenges for inkjet fabrication of active layers, electron- as well as hole-transport layers and electrodes. An outlook on the perspectives that the combination of printed photovoltaics and inkjet has to offer concludes the chapter.<br
Keywords: Inkjet; organic photovoltaics; OPV; OSC; perovskite photovoltaics; PSC; printed solar cell; solar module; flexible electrode

In Situ Probing the Crystallization Kinetics in Gas-Quenching-Assisted Coating of Perovskite Films - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Jang, Dongju; Le Corre, Vincent Marc; García Cerrillo, José; Ronsin, Olivier J.J.; Yang, Fu; Guo, Fei; Zhang, Kaicheng; Lüer, Larry; Harting, Jens; et al. (Advanced Energy Materials, 2024)
The pursuit of commercializing perovskite photovoltaics is driving the development of various scalable perovskite crystallization techniques. Among them, gas quenching is a promising crystallization approach for high-throughput deposition of perovskite films. However, the perovskite films prepared by gas-quenching assisted blade coating are susceptible to the formation of pinholes and frequently show inferior crystallinity if the interplay between film coating, film drying, and crystallization kinetics is not fully optimized. That arguably requires a thorough understanding of how single processing steps influence the crystallization kinetics of printed perovskite films. Here, in situ optical spectroscopies are integrated into a doctor-blading setup that allows to real-time monitor film formation during the gas-quenching process. It is found that the essential role of gas quenching treatment is in achieving a smooth and compact perovskite film by controlling the nucleation rate. Moreover, with the assistance of phase-field simulations, the role of excessive methylammonium iodide is revealed to increase grain size by accelerating the crystal growth rate. These results show a tailored control of crystal growth rate is critical to achieving optimal film quality, leading to fully printed solar cells with a champion power conversion efficiency of 19.50% and mini solar modules with 15.28% efficiency are achieved.
CRIS-Team Scopus Importer:2024-01-12
Keywords: blade coating; fully printed perovskite photovoltaics; gas quenching; in situ techniques; phase-field simulations

Large-area organic photovoltaic modules with 14.5% certified world record efficiency - Basu, Robin; Gumpert, Fabian; Lohbreier, Jan; Morin, Pierre Olivier; Vohra, Varun; Liu, Yang; Zhou, Yinhua; Brabec, Christoph; Egelhaaf, Hans-Joachim; Distler, Andreas (Joule, 2024)
Organic photovoltaics (OPVs) have experienced a significant increase in power conversion efficiency (PCE) recently, now approaching 20% on small-cell level. Since the efficiencies on the module level are still substantially lower, focused upscaling research is necessary to reduce the gap between cells and modules. In this work, we present the upscaling of PM6:Y6-C12:PC61BM-based devices, processed in ambient air from non-halogenated solvents, from small-area cells to large-area modules with barely any performance loss. Supported by computational fluid dynamics simulations, an accelerated blade coating process that enables homogeneous coatings with <5% thickness deviation over 200 cm² is developed. Additional finite element method simulations are used to optimize the module layout and minimize the inevitable losses caused by electrode resistances and inactive interconnect areas to 1.9% and 3.5%, respectively. Finally, a 204-cm² OPV module with a certified PCE of 14.5% (15.0% on active area) is fabricated, which constitutes the new world record.
CRIS-Team Scopus Importer:2024-04-05
Keywords: certified world record efficiency; FEM simulations; laser patterning; OPVs; organic photovoltaics; process optimization; solar modules; solution-processed in ambient air

Long term outdoor performance evaluation of printed semitransparent organic photovoltaic modules for BIPV/BAPV applications - Feroze, Sarmad; Distler, Andreas; Dong, Lirong; Wagner, Michael; Channa, Iftikhar Ahmed; Hoga, Felix; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2024)
Recently, organic photovoltaics (OPV) have achieved power conversion efficiencies (PCE) above 20% thus coming closer to market entry. Building-integrated photovoltaics (BIPV) and building-attached photovoltaics (BAPV) are two key areas where the functional advantages of both OPV and BIPV/BAPV complement each other and thus could pave the way for market penetration of OPV. Herein, we report on large-area, all-solution-processed flexible OPV modules manufactured by a fully roll-to-roll (R2R) method with high levels of process repeatability. The OPV modules show an accelerated lifetime (ALT) of more than 1000 h and 2800 h under the ISOS-L2 and ISOS-D3 testing conditions, respectively. Long-term outdoor monitoring of the OPV modules was conducted in a typical central European climate, considering two distinct mounting angles that hold significant relevance for BIPV installations i.e., 45° inclination with respect to the ground (representing the optimal tilt angle of the site) and 90° vertical mounting (as mostly encountered in BIPV façades). The ISOS-O2 protocol was used as the test standard for outdoor monitoring. The results show that the OPV modules can offer higher daily specific energy yields (YFD), i.e., higher ratios of daily energy yield and STC WP capacity of the module, than a reference mono-crystalline (m-Si) module for BIPV installations typical of a rooftop case (i.e., 45°), whereas for façade integrated cases (i.e., 90°), OPV modules offer YFD values identical to that of m-Si modules. Detailed laboratory investigations reveal that the higher YFD values of the OPV modules at 45° mounting stems from their negligible temperature coefficient of −0.008% °C−1, whereas at 90° mounting, the angle-dependent response of the modules plays a crucial role.
CRIS-Team Scopus Importer:2025-02-04

Low Temperature Processed Fully Printed Efficient Planar Structure Carbon Electrode Perovskite Solar Cells and Modules - Yang, Fu; Dong, Lirong; Jang, Dongju; Saparov, Begench; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
Scalable deposition processes at low temperature are urgently needed for the commercialization of perovskite solar cells (PSCs) as they can decrease the energy payback time of PSCs technology. In this work, a processing protocol is presented for highly efficient and stable planar n–i–p structure PSCs with carbon as the top electrode (carbon-PSCs) fully printed at fairly low temperature by using cheap materials under ambient conditions, thus meeting the requirements for scalable production on an industrial level. High-quality perovskite layers are achieved by using a combinatorial engineering concept, including solvent engineering, additive engineering, and processing engineering. The optimized carbon-PSCs with all layers including electron transport layer, perovskite, hole transport layer, and carbon electrode which are printed under ambient conditions show efficiencies exceeding 18% with enhanced stability, retaining 100% of their initial efficiency after 5000 h in a humid atmosphere. Finally, large-area perovskite modules are successfully obtained and outstanding performance is shown with an efficiency of 15.3% by optimizing the femtosecond laser parameters for the P2 line patterning. These results represent important progress toward fully printed planar carbon electrode perovskite devices as a promising approach for the scaling up and worldwide application of PSCs.
CRIS-Team Scopus Importer:2021-06-18
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; perovskite solar cells

Material Strategies to Accelerate OPV Technology Toward a GW Technology - Brabec, Christoph; Distler, Andreas; Du, Xiaoyan; Egelhaaf, Hans-Joachim; Hauch, Jens; Heumüller, Thomas; Li, Ning (Advanced Energy Materials, 2020)
With the rise of the solar power century, photovoltaic applications and installations will go beyond the traditional green field power plants and enter any aspect of daily life. Organic photovoltaics (OPVs) demonstrate certified cell efficiencies of over 17% and are expected to contribute to versatile applications powered by solar energy, for instance, applications rely on flexibility, transparency, color management, or integrability. In this work, the progress of OPV technology is briefly reviewed and the material strategies to accelerate OPV technology toward a GW era are analyzed. In addition to the exciting efficiency values achieved for small area devices, there are many important criteria deciding the success of OPV technology. By taking into consideration the synthetic complexity of OPV materials and the operational stability of OPV devices, the industrial figure of merit (i-FoM) is proposed as a fast and reliable method to verify the true potential of a novel material. Furthermore, “soft” key performance indicators are introduced, such as toxicity, flexibility, transparency, processing, which require different development strategies to reflect the potential of OPV technology for specific applications.
CRIS-Team Scopus Importer:2020-10-09
Keywords: device operational stability; organic photovoltaics; organic solar modules; synthetic complexity

Mechanical Failure of Transparent Flexible Silver Nanowire Networks for Solar Cells using 3D X-Ray Nano Tomography and Electron Microscopy - Englisch, Silvan; Wirth, Janis; Schrenker, Nadine; Tam, Kai Cheong; Egelhaaf, Hans-Joachim; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2018)

On the theoretical framework for meniscus-guided manufacturing of large-area OPV modules - Gumpert, Fabian; Janßen, Annika; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim; Lohbreier, Jan; Distler, Andreas (Progress in Organic Coatings, 2024)
For the manufacturing of thin films of solution-processable organic semiconductors, e.g. for organic photovoltaics (OPV), meniscus guided-coating techniques are the method of choice for large-scale industrial applications. However, the process requires an in-depth understanding of the respective fluid dynamics to control the resulting film thickness. In this article, we derive an analytical expression to describe the layer thickness of coatings manufactured with a trapezoidal-shaped applicator as a function of various fluid and process parameters. The analytical calculations are compared with results from computational fluid dynamics (CFD) simulations and experimental data for an industrially relevant OPV active material system. The good agreement of all three approaches demonstrates the potential of the analytical and simulative methods to minimize the number of time- and resource-consuming experiments. Furthermore, our theoretical model can be used to enhance the homogeneity of large-area coatings by means of an acceleration profile of the applicator that can compensate for the liquid loss during the coating process. The respective analytical expression is validated by simulated and experimentally obtained data for long-distance coatings. Finally, this approach is used to fabricate a large-area OPV module with new world record efficiency.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Accelerated coating velocity; Analytical description; Computational fluid dynamics; Meniscus-guided coating; Organic photovoltaics; Thin films

Organic photovoltaic modules with new world record efficiencies - Distler, Andreas; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2020)
During the last years, the development of new active materials has led to constant improvement in the power conversion efficiency (PCE) of solution-processed organic photovoltaics (OPV) to nowadays record values above 17% on small lab cells. In this work, we show the developments and results of a successful upscaling of such highly efficient OPV systems to the module level on large areas, which yielded two new certified world record efficiencies, namely, 12.6% on a module area of 26 cm2 and 11.7% on a module area of 204 cm2. The decisive developments leading to this achievement include the optimization of the module layout as well as the high-resolution short-pulse (nanosecond) laser structuring processes involved in the manufacturing of such modules. By minimizing the inactive areas within the total module area that are used for interconnecting the individual solar cells of the module in series, geometric fill factors of over 95% have been achieved. A production yield of 100% working modules during the manufacturing of these modules and an extremely narrow distribution of the final PCE values underline the excellent process control and reproducibility of the results. The new developments and their implementation into the production process of the record OPV modules are described in detail, along with the challenges that arose during this development. Finally, dark lock-in thermography (DLIT), electroluminescence (EL), and photoluminescence (PL) measurements of the record module are presented.
CRIS-Team Scopus Importer:2020-09-25
Keywords: certified power conversion efficiency (PCE); laser patterning; organic photovoltaics (OPV); solar modules; world record

Overcoming Moisture-Induced Degradation in Organic Solar Cells - Wachsmuth, Josua; Distler, Andreas; Deribew, Dargie; Salvador, Michael Filipe; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Engineering Materials, 2023)
Unencapsulated organic solar cells are prone to severe performance losses in the presence of moisture. Accelerated damp heat (85 °C/85% RH) studies are presented and it is shown that the hygroscopic hole-transporting PEDOT:PSS layer is the origin of device failure in the case of prototypical inverted solar cells. Complementary measurements unveil that under these conditions a decreased PEDOT:PSS work function along with areas of reduced electrical contact between active layer and hole-transport layer are the main factors for device degradation rather than a chemical reaction of water with the active layer. Replacements for PEDOT:PSS are explored and it is found that tungsten oxide (WO3) or phosphomolybdic acid (PMA)—materials that can be processed from benign solvents at room temperature—yields comparable performance as PEDOT:PSS and enhances the resilience of solar cells under damp heat. The stability trend follows the order PEDOT:PSS << WO3 < PMA, with PEDOT:PSS-based devices failing after few minutes, while PMA-based devices remain nearly pristine over several hours. PMA is thus proposed as a robust, solution-processable hole extraction layer that can act as a one to one replacement of PEDOT:PSS to achieve organic solar cells with significantly improved longevity.
CRIS-Team Scopus Importer:2023-06-02
Keywords: degradation and stability; humidity; organic photovoltaics; phosphomolybdic acid; solution processed

Over one-micron-thick void-free perovskite layers enable highly efficient and fully printed solar cells - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Distler, Andreas; Li, Chaohui; Forberich, Karen; Tian, Jingjing; Hemasiri, Naveen Harindu; Liu, Chao; Zhang, Jiyun; Yang, Fu; Le Corre, Vincent Marc; et al. (Energy and Environmental Science, 2025)
Commercialization of perovskite photovoltaics hinges on the successful transition from laboratory-scale fabrication to industrial-scale manufacturing. A key challenge in fully printed perovskite solar cells with non-reflecting back electrodes is the deposition of high-quality, over-one-micron-thick perovskite layers to minimize photocurrent losses from incomplete light absorption. However, the formation of voids at the substrate/perovskite interface impedes the fabrication of such layers. Here, phase-field simulations reveal that the bottom voids originate from trapped residual solvents, driven by nanocrystal aggregation at the liquid-vapor interface during drying. Guided by these insights, we introduce a two-dimensional (2D) perovskite layer-assisted growth strategy to promote heterogeneous nucleation at the substrate, accelerating 3D perovskite crystallization and preventing solvent entrapment. This strategy enables the formation of highly crystalline, monolithic perovskite films exceeding one micrometer in thickness. The resulting void-free films maximize photocurrent extraction, achieving power conversion efficiencies of 19.9% on rigid substrates and 17.5% on flexible substrates in fully printed perovskite solar cells with non-reflecting carbon electrodes.
CRIS-Team Scopus Importer:2025-05-30

Perfluoroalkylsulfonyl ammonium for humidity- resistant printing high-performance phase-pure FAPbI3 perovskite solar cells and modules - Chen, Xining; Yang, Fu; Yuan, Linhao; Huang, Shihao; Gu, Hao; Wu, Xiaoxiao; Shen, Yunxiu; Chen, Yujin; Li, Ning; Egelhaaf, Hans-Joachim; Brabec, Christoph; Zhang, Rui; et al. (Joule, 2024)
High-quality phase-pure formamidinium lead triiodide (FAPbI3) perovskite film needs to be fabricated under strict control of the surrounding atmosphere, which becomes more rigorous when large-area FAPbI3 film is involved, leading to high-performance FAPbI3 perovskite solar cells and modules predominantly carried out in an inert gas-filled atmosphere. In this work, we propose a scalable printing strategy for the large-area high-quality phase-pure FAPbI3 film under a high-humidity atmosphere (up to 75% ± 5% relative humidity) by regulating the perovskite precursor ink with a functional perfluoroalkylsulfonyl quaternary ammonium iodide. This approach decreases the energy barriers of cubic phase formation and heterogeneous nucleation, thereby regulating the FAPbI3 crystallization. The printed photovoltaic small-area cells and large-area modules achieved remarkable power conversion efficiencies of 24.37% and 22.00%, respectively. Specifically, the unencapsulated device exhibits superior operational stability with T90 > 1,060 h, ambient stability with T90 > 2,020 h, and thermal stability with T90 > 2,350 h.
CRIS-Team Scopus Importer:2024-07-19
Keywords: blade coating; film formation; humid atmosphere; perovskite crystallization; perovskite solar cells; scalable printing; solar module; stable perovskite

Phase-Field Simulation of Liquid-Vapor Equilibrium and Evaporation of Fluid Mixtures - Ronsin, Olivier; Jang, Dong Ju; Egelhaaf, Hans-Joachim; Brabec, Christoph; Harting, Jens (ACS Applied Materials and Interfaces, 2021)
In solution processing of thin films, the material layer is deposited from a solution composed of several solutes and solvents. The final morphology and hence the properties of the film often depend on the time needed for the evaporation of the solvents. This is typically the case for organic photoactive or electronic layers. Therefore, it is important to be able to predict the evaporation kinetics of such mixtures. We propose here a new phase-field model for the simulation of evaporating fluid mixtures and simulate their evaporation kinetics. Similar to the Hertz-Knudsen theory, the local liquid-vapor (LV) equilibrium is assumed to be reached at the film surface and evaporation is driven by diffusion away from this gas layer. In the situation where the evaporation is purely driven by the LV equilibrium, the simulations match the behavior expected theoretically from the free energy: for evaporation of pure solvents, the evaporation rate is constant and proportional to the vapor pressure. For mixtures, the evaporation rate is in general strongly time-dependent because of the changing composition of the film. Nevertheless, for highly nonideal mixtures, such as poorly compatible fluids or polymer solutions, the evaporation rate becomes almost constant in the limit of low Biot numbers. The results of the simulation have been successfully compared to experiments on a polystyrene-toluene mixture. The model allows to take into account deformations of the liquid-vapor interface and, therefore, to simulate film roughness or dewetting.
CRIS-Team Scopus Importer:2021-12-24
Keywords: evaporation; film drying; liquid-vapor equilibrium; phase-field

Precursor-Engineered Volatile Inks Enable Reliable Blade-Coating of Cesium–Formamidinium Perovskites Toward Fully Printed Solar Modules - Du, Tian; Rehm, Viktor; Qiu, Shudi; Pal, Subhajit; Jang, Dongju; Peng, Zijian; Zhang, Jiyun; Yuan, Haozhen; Briscoe, Joe; Heiß, Wolfgang; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Science, 2024)
Reliable fabrication of large-area perovskite films with antisolvent-free printing techniques requires high-volatility solvents, such as 2-methoxyethanol (2ME), to formulate precursor inks. However, the fabrication of high-quality cesium–formamidinium (Cs–FA) perovskites has been hampered using volatile solvents due to their poor coordination with the perovskite precursors. Here, this issue is resolved by re-formulating a 2ME-based Cs0.05FA0.95PbI3 ink using pre-synthesized single crystals as the precursor instead of the conventional mixture of raw powders. The key to obtaining high-quality Cs–FA films lies in the removal of colloidal particles from the ink and hence the suppression of colloid-induced heterogeneous nucleation, which kinetically facilitates the growth of as-formed crystals toward larger grains and improved film crystallinity. Employing the precursor-engineered volatile ink in the vacuum-free, fully printing processing of solar cells (with carbon electrode), a power conversion efficiency (PCE) of 19.3%, a T80 (80% of initial PCE) of 1000 h in ISOS-L-2I (85 °C/1 Sun) aging test and a substantially reduced bill of materials are obtained. The reliable coating methodology ultimately enables the fabrication of carbon-electrode mini solar modules with a stabilized PCE of 16.2% (average 15.6%) representing the record value among the fully printed counterparts and a key milestone toward meeting the objectives for a scalable photovoltaic technology.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cesium formamidinium perovskite; reliable blade coating; single crystals; solar module; volatile ink

Predicting layer thicknesses by numerical simulation for meniscus-guided coating of organic photovoltaics - Gumpert, Fabian; Janßen, Annika; Brabec, Christoph; Egelhaaf, Hans-Joachim; Lohbreier, Jan; Distler, Andreas (Engineering Applications of Computational Fluid Mechanics, 2023)
To achieve maximum efficiency in organic photovoltaics (OPV), functional layers with uniform and exactly predefined thickness are required. An in-depth understanding of the coating process is therefore crucial for an accurate process control. In this paper, the meniscus-guided blade coating process, which is the most commonly used process for the manufacturing of organic electronics, is investigated by experimental and numerical methods. A computational fluid dynamics (CFD) model is created to simulate the coating behaviour of P3HT:O IDTBR, an industrial state-of-the-art active material system used in OPV, and its results' independence of numerical parameters is ensured. In particular, the influence of the coating velocity and the initially injected fluid volume on the resulting wet film thickness is studied. The developed CFD analysis is able to reproduce the experimental results with very high accuracy. It is found that the film thickness follows a power law dependence on the velocity (˜v 2/3) and a linear dependence on the ink volume (˜V). Accordingly, an analytical expression based on our theoretical considerations is presented, which predicts the wet film thickness as a function of the coating velocity and the ink volume only based on easily accessible ink properties. Consequently, this CFD model can effectively substitute time-consuming and expensive experiments, which currently have to be performed manually in the laboratory for a multitude of novel material systems, and thus supports highly accelerated material research. Moreover, the results of this work can be used to achieve homogeneous large-area coatings by utilising accelerated blade coating.
CRIS-Team Scopus Importer:2023-08-18
Keywords: coating techniques; COMSOL multiphysics; Numerical simulation; organic photovoltaics; renewable energy; thin films

Printing High-Quality Formanidinum Lead Triiodide Films: Understanding the Critical Role of α-Phase Nucleation Before Thermal Annealing - Qiu, Shudi; Dong, Lirong; Jang, Dongju; Yang, Fu; García Cerrillo, José; Li, Chaohui; Xie, Zhiqiang; Luo, Junsheng; Guo, Fei; Distler, Andreas; Du, Tian; Brabec, Christoph; et al. (Advanced Energy Materials, 2024)
Upscaling the coating of formamidinium lead triiodide (FAPbI3) thin film is essential to realizing full printing and thereby roll-to-roll production of perovskite photovoltaics. However, thin-film FAPbI3 processed from antisolvent-free, printing methods suffer from undesirable degradation to the non-photoactive phase, particularly in ambient processing conditions. Here, the most critical stage in thin-film processing is identified as the gas-quenching treatment of the as-cast wet film. It is crucial to achieve both the nucleation of α-phase nanocrystals and their sufficient growth at room temperature, which are indispensable for templating the growth of a highly crystalline and stable α-FAPbI3 film during subsequent thermal annealing. The gas-quenching-treated film without these α-phase nanocrystals can only be converted to meta-stable α-FAPbI3 by thermal annealing. By precisely identifying the spontaneous doping of cesium ion (Cs+) as a key factor in triggering α-FAPbI3 nucleation and the role of chloride ion (Cl−) in enhancing nanocrystal growth, a generalized mechanism for additive engineering for the precursor ink is theorized. The identified mechanism translates to a power conversion efficiency of 19.36% for fully printed carbon-electrode solar cells, 16.23% for carbon-electrode minimodules, and excellent operational stability, showing the promising potential of this proposed fabrication route in the upscaling of perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: carbon-electrode; cesium ion; FAPbI; nucleation; perovskite photovoltaics

Rational Interface Design and Morphology Control for Blade-Coating Efficient Flexible Perovskite Solar Cells with a Record Fill Factor of 81% - Wang, Zhen; Zeng, Linxiang; Zhang, Cuiling; Lu, Yuanlin; Qiu, Shudi; Wang, Chuan; Liu, Chong; Pan, Lijun; Wu, Shaohang; Hu, Jinlong; Liang, Guangxing; Fan, Ping; et al. (Advanced Functional Materials, 2020)
Halide perovskites are one of the ideal photovoltaic materials for constructing flexible solar devices due to relatively high efficiencies for low-temperature solution-processed devices. However, the overwhelming majority of flexible perovskite solar cells are produced using spin coating, which represents a major hurdle for upscaling. Here, a scalable approach is reported to fabricate efficient and robust flexible perovskite solar cells on a polymer substrate. Thiourea is introduced into perovskite precursor solution to modulate the crystal growth, resulting in dense and uniform perovskite thin films on rough surfaces. As a decisive step, a cascade energy alignment is realized for the hole extraction layer by rationally designing a bilayer interface comprised of PEDOT:PSS/PTAA with a distinct offset in the highest occupied molecular orbital levels, enabling markedly enhanced charge extraction and spectral response. An efficiency as high as 19.41% and a record fill factor up to 81% are achieved for flexible perovskite devices processed by a scalable printing method. Equally important, the bilayer interface reinforces the bendability of the indium tin oxide substrate, leading to enhanced mechanical robustness of the flexible devices. These results underpin the importance of morphology control and interface design in constructing high-performance flexible perovskite solar cells.
CRIS-Team Scopus Importer:2020-07-10
Keywords: bilayer interface; blade coating; cascade energy alignment; flexible solar cells; perovskite

Renewed Prospects for Organic Photovoltaics - Zhang, Guichuan; Lin, Francis R.; Qi, Feng; Heumüller, Thomas; Distler, Andreas; Egelhaaf, Hans-Joachim; Li, Ning; Chow, Philip C. Y.; Brabec, Christoph; Jen, Alex K. -Y.; Yip, Hin-Lap (Chemical Reviews, 2022)
Organic photovoltaics (OPVs) have progressed steadily through three stages of photoactive materials development: (i) use of poly(3-hexylthiophene) and fullerene-based acceptors (FAs) for optimizing bulk heterojunctions; (ii) development of new donors to better match with FAs; (iii) development of non-fullerene acceptors (NFAs). The development and application of NFAs with an A-D-A configuration (where A = acceptor and D = donor) has enabled devices to have efficient charge generation and small energy losses (Eloss < 0.6 eV), resulting in substantially higher power conversion efficiencies (PCEs) than FA-based devices. The discovery of Y6-type acceptors (Y6 = 2,2'-((2Z,2'Z)-((12,13-bis (2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]-thiadiazolo [3,4-e]-thieno- [2 ",3 ":4',5']thieno-[2',3':4,5]pyrrolo-[3,2-g]thieno-[2',3':4,5]thieno-[3,2-b]indole-2,10- diyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))-dimalononitrile) with an A-DA' D-A configuration has further propelled the PCEs to go beyond 15% due to smaller Eloss values (& SIM;0.5 eV) and higher external quantum efficiencies. Subsequently, the PCEs of Y6-series single-junction devices have increased to > 19% and may soon approach 20%. This review provides an update of recent progress of OPV in the following aspects: developments of novel NFAs and donors, understanding of the structure-property relationships and underlying mechanisms of state-of-the-art OPVs, and tasks underpinning the commercialization of OPVs, such as device stability, module development, potential applications, and high-throughput manufacturing. Finally, an outlook and prospects section summarizes the remaining challenges for the further development of OPV technology.
CRIS-Team WoS Importer:2022-08-26

Resolving a Critical Instability in Perovskite Solar Cells by Designing a Scalable and Printable Carbon Based Electrode-Interface Architecture - Mashhoun, Sara; Hou, Yi; Chen, Haiwei; Tajabadi, Fariba; Taghavinia, Nima; Egelhaaf, Hans-Joachim; Brabec, Christoph (Advanced Energy Materials, 2018)
Thin-film solar cells based on hybrid organo-halide lead perovskites achieve over 22% power conversion efficiency (PCE). A photovoltaic technology at such high performance is no longer limited by efficiency. Instead, lifetime and reliability become the decisive criteria for commercialization. This requires a standardized and scalable architecture which does fulfill all requirements for larger area solution processing. One of the most highly demanded technologies is a low temperature and printable conductive ink to substitute evaporated metal electrodes for the top contact. Importantly, that electrode technology must have higher environmental stability than, for instance, an evaporated silver (Ag) electrode. Herein, planar and entirely low-temperature-processed perovskite devices with a printed carbon top electrode are demonstrated. The carbon electrode shows superior photostability compared to reference devices with an evaporated Ag top electrode. As hole transport material, poly (3′hexyl thiophene) (P3HT) and copper(I) thiocyanate (CuSCN), two cost-effective and commercially available p-type semiconductors are identified to effectively replace the costlier 2,2′,7,7′-Tetrakis-(N,N-di-4-methoxyphenylamino)- 9,9′-spirobifluorene (spiro-MeOTAD). While methylammonium lead iodide (MAPbI3)-based perovskite solar cells (PSCs) with an evaporated Ag electrode degrade within 100 h under simulated sunlight (AM 1.5), fully solution-processed PSCs with printed carbon electrodes preserve more than 80% of their initial PCE after 1000 h of constant illumination.<br
Keywords: carbon electrodes; hole transporting material; stability; perovskite solar cells; photovoltaic devices

Robot-Based High-Throughput Screening of Antisolvents for Lead Halide Perovskites - Gu, Ening; Tang, Xiaofeng; Langner, Stefan; Duchstein, Patrick; Zhao, Yicheng; Levchuk, Ievgen; Kalancha, Violetta; Stubhan, Tobias; Hauch, Jens; Egelhaaf, Hans-Joachim; Zahn, Dirk; Osvet, Andres; et al. (Joule, 2020)
Solution-based processing of photovoltaic materials has important advantages, including lower overall costs and easier upscaling of fabrication, where the solvents play an essential role. Antisolvent crystallization technique is often applied to achieve high-quality perovskite materials. However, the basic chemistry of the solvent-antisolvent crystallization is still not well understood. Besides, common antisolvents are toxic, and their number is limited. In this work, a novel robot-based method was used to screen the efficient antisolvents for different solvent-perovskite systems. 336 combinations of perovskite-solvent-antisolvent could be prepared and characterized by the integrated robotic platform in 2 days. In addition, we provided a detailed working mechanism of the solvent-antisolvent crystallization approach. Furthermore, hundreds of potential antisolvents were proposed based on high-throughput screening and simulation. Verification tests match well with theory, and all reported antisolvents used for photovoltaic device optimizations are within our predicted range of the Hansen space, indicating that the predictions are reliable. In terms of solution-processed lead halide perovskite optoelectrical materials, suitable antisolvent is essential for the crystallization and properties of final products. Conventional experiments of antisolvent selections are based on the manual time-consuming trial-error methods, which cannot meet today's increasing demands. In this work, a robot-based method was used to screen the antisolvents for different solvent-perovskite systems in a high-throughput manner to study the influence of interactions among the solvent molecules, cations, metal-halides, and antisolvents, to build an informative database, and to reveal the working mechanism and selection criteria of antisolvents. Besides, simulations based on the screening results provide hundreds of potential antisolvents. Corresponding verification tests evidenced that our predictions are reliable and vital for designing future efficient mixed solvent systems for the fabrication of perovskite optoelectrical materials. A robotic platform is adopted to conduct a comprehensive solvent engineering for making lead halide perovskites in a high-throughput manner. Deeper insights into the working mechanisms and selection criteria of antisolvents are investigated and summarized. In addition, a reliable antisolvent database is established, and verification tests match well with the theory. Furthermore, our work provides significant guidance for designing functional and environment-friendly mixed solvent systems to fabricate high-quality perovskite materials or devices.
CRIS-Team Scopus Importer:2020-08-21
Keywords: antisolvents; automated research; high-throughput method; lead halide complexes; lead halide perovskite; solvent engineering

Roll-to-Roll Deposition of Wide-Bandgap CsFAPbBr3 Perovskite Solar Cells in Ambient Air with Optimized Ink Formulation - Jafarzadeh, Farshad; Dong, Lirong; Jang, Dongju; Wagner, Michael; Koch, Giulio; Qiu, Shudi; Feroze, Sarmad; García Cerrillo, José; Brabec, Christoph; Di Carlo, Aldo; Brunetti, Francesca; Egelhaaf, Hans-Joachim; et al. (Solar RRL, 2024)
The growing demand for sustainable energy solutions has made the development of scalable, efficient, and cost-effective perovskite solar cells (PSCs) increasingly important. Wide-bandgap perovskites (WB-PSCs) stand out due to their efficiency in low-light conditions and their use in tandem solar cells. WB-PSCs are currently behind conventional PSCs in upscaling, with limited success in printing wide bandgap PSCs. Developing upscaling methods is essential to fully realize their potential in the renewable energy sector. This research addresses the development of roll-to-roll (R2R) slot-die coating of Cs0.05FA0.95PbBr3-based WB-PSCs by focusing on improving the film formation process and ink formulation. By adding optimal concentration of CsBr and performing in situ characterization, we obtained Cs0.05FA0.95PbBr3 films with enhanced morphology and crystallinity in ambient conditions (50% RH), without inducing secondary phase formation. In addition, slot-die coating defects are eliminated through introducing DMSO: Butanol (9:1) solvent system. The R2R coated wide-bandgap PSCs reaches a power conversion efficiency (PCE) of up to 8.97% under 1-sun conditions and 18.3% PCE under indoor conditions. The corresponding R2R coated modules with a 5 × 5 cm2 active area achieve a PCE of 5.8%, representing a crucial step towards the high-throughput, cost-effective production of perovskite solar modules.
CRIS-Team Scopus Importer:2024-10-11
Keywords: ambient deposition; ink formulation; roll-to-roll; slot-die coating; wide-bandgap perovskite solar cells

Shy Organic Photovoltaics: Digitally Printed Organic Solar Modules With Hidden Interconnects - Maisch, Philipp; Tam, Kai Cheong; Schilinsky, Pavel; Egelhaaf, Hans-Joachim; Brabec, Christoph (Solar RRL, 2018)
One of the biggest attractions of the organic photovoltaics (OPV) technology is the easiness with which it can be integrated. However, despite its semitransparency and wide variety of colors, a major unresolved challenge is to fabricate optically inconspicuous organic photovoltaic modules (OPV-M) that can be integrated into visually demanding products. This is dominantly due to the visual obstruction from Z-interconnection lines inherent to module processing with classical patterning methods. We now present for the first time a solution to this problem, which utilizes a visually seamless interconnection method to elegantly minimize the conspicuity of the interconnection regime. We realize such invisible interconnects by inkjet printing highly conductive silver lines, which penetrate the solar cell stack and form an electrical connection between adjacent cells. A combined characterization approach utilizing in-depth electrical characterization and finite element (FEM) simulation rationalizes the excellent electrical cell-to-cell contact established with this interconnection technology. We combine this technology with a variable-geometry module design into an innovative digital inkjet printing platform for the production of state-of-the art but visually attractive solar modules. The full potential of this concept is demonstrated by a fully inkjet printed arbitrarily shaped OPV-M portrait<br
Keywords: inkjet printing; organic photovoltaics; printed electronics; shy photovoltaics; upscaling

Silver Electrodes for Organic Solar Cells Printed via Laser-Induced Forward Transfer - Bibrack, Max; Distler, Andreas; Wagner, Michael; Forberich, Karen; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy Technology, 2025)
Laser-induced forward transfer (LIFT) is presented as a new, contactless, and roll-to-roll compatible method for the deposition of silver top electrodes for organic solar cells (OSCs). Employing a nanosecond laser, highly reflective silver electrodes are printed by LIFT onto OSCs with P3HT:o-IDTBR bulk heterojunction layers. Upon optimization of ink composition, source film thickness, and laser parameters, the resulting organic solar cells reach efficiencies of more than 5%, which are similar to those of reference devices with vapor-deposited silver electrodes.
CRIS-Team Scopus Importer:2025-02-04
Keywords: laser-induced forward transfer process; nanosecond laser; organic photovoltaics; printable electrodes; silver nanoparticles

Simplifying contact-layer design for high-throughput printing of flexible perovskite photovoltaics - Dong, Lirong; Qiu, Shudi; Feroze, Sarmad; Wagner, Michael; Kasian, Olga; Peisert, Heiko; Kosasih, Felix U.; Ducati, Caterina; García Cerrillo, José; Tian, Jingjing; Li, Chaohui; Jang, Dongju; et al. (Energy and Environmental Science, 2024)
The realization of scalable roll-to-roll production processes for metal-halide perovskite modules is a necessary development for transferring developments and technologies from the lab to the fab. Before that, it is imperative to close the efficiency gap not only between the devices fabricated on rigid substrates versus flexible substrates, but also between solar cells to solar modules. In this regard, a critical assessment of device architectures that are more compatible to scalable fabrication is needed. Obviously, the adaption to mass manufacturing must not negatively impact device performance and operational stability. Here, by investigating the properties of printed fullerene-based phosphonic acid dipole interface layers, we establish simplified self-assembled monolayer (SAM) based n-i-p architectures without any charge extraction layers other than SAMs, which are easily processed and are thus ideally suited for mass production. We show that a contact-layer design with a printed fullerene-based SAM that has phosphonic acid is sufficient to provide good charge selectivity and to minimize interface recombination at the bottom electrode. We further show that the same SAM molecule can be used as a p-type interface material on top of the perovskite. This simplified contact-layer design, which is based on one material for both hole and electron work-function adaption is successfully integrated into our fully printed module process comprising the deposition of a carbon top electrode. The achieved open-circuit voltage exceeds 1.1 V, and the fill factor surpasses 70%, highlighting the potential of this novel interface design concept for both rigid and flexible substrates.
CRIS-Team Scopus Importer:2024-09-06

Simulation of perovskite thin layer crystallization with varying evaporation rates - Majewski, M.; Qiu, Shudi; Ronsin, O.; Lüer, Larry; Le Corre, Vincent Marc; Du, Tian; Brabec, Christoph; Egelhaaf, Hans-Joachim; Harting, J. (Materials Horizons, 2024)
Perovskite solar cells (PSC) are promising potential competitors to established photovoltaic technologies due to their superior efficiency and low-cost solution processability. However, the limited understanding of the crystallization behaviour hinders the technological transition from lab-scale cells to modules. In this work, advanced phase field (PF) simulations of solution-based film formation are used for the first time to obtain mechanistic and morphological information that is experimentally challenging to access. The well-known transition from a film with many pinholes, for a low evaporation rate, to a smooth film, for high evaporation rates, is recovered in simulation and experiment. The simulation results provide us with an unprecedented understanding of the crystallization process. They show that supersaturation and crystallization confinement effects determine the final morphology. The ratio of evaporation to crystallization rates turns out to be the key parameter driving the final morphology. Increasing this ratio is a robust design rule for obtaining high-quality films, which we expect to be valid independently of the material type.
CRIS-Team Scopus Importer:2024-11-22

Solution processed oxygen and moisture barrier based on glass flakes for encapsulation of organic (opto-) electronic devices - Channa, Iftikhar Ahmed; Distler, Andreas; Scharfe, Benedikt; Feroze, Sarmad; Forberich, Karen; Lipovsek, Benjamin; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2021)
The concept of transparent barriers against oxygen and water based on polymer films filled with glass flakes is presented. Barriers are prepared by casting polyvinyl butyral (PVB) films containing glass flakes of different aspect ratios (ARs) at different loadings to systematically study the effect of these parameters on barrier quality and optical transmission. It is found that the glass flakes are distributed homogeneously in the PVB film, with an almost perfect orientation of the long axes of the platelets parallel to the film surface. For glass flakes having an AR of 2000, barrier films with optical transmittance exceeding 85% and water vapor transmission rates of 0.14 g m(-2) d(-1) are obtained at a glass loading of 25 vol%. The haze of the glass flake filled PVB films, which is mainly due to surface roughness of the films according to optical simulations, is reduced by coating a smoothing layer on top. The barrier properties persist even after 20 000 cycles of bending at a radius of 3 cm. The lifetime of organic solar cells increases to beyond 1000 h under damp heat conditions as well as under constant illumination, when the devices are encapsulated with the PVB/glass flake composite films.
CRIS-Team WoS Importer:2021-06-25
Keywords: optical simulations; organic solar cell encapsulation; flexible barriers; glass flakes; polyvinyl butyral

The 2021 flexible and printed electronics roadmap - Bonnassieux, Yvan; Brabec, Christoph; Cao, Yong; Carmichael, Tricia Breen; Chabinyc, Michael L.; Cheng, Kwang Ting; Cho, Gyoujin; Chung, Anjung; Cobb, Corie L.; Distler, Andreas; Egelhaaf, Hans-Joachim; Grau, Gerd; et al. (Flexible and Printed Electronics, 2021)
This roadmap includes the perspectives and visions of leading researchers in the key areas of flexible and printable electronics. The covered topics are broadly organized by the device technologies (sections 1–9), fabrication techniques (sections 10–12), and design and modeling approaches (sections 13 and 14) essential to the future development of new applications leveraging flexible electronics (FE). The interdisciplinary nature of this field involves everything from fundamental scientific discoveries to engineering challenges; from design and synthesis of new materials via novel device design to modelling and digital manufacturing of integrated systems. As such, this roadmap aims to serve as a resource on the current status and future challenges in the areas covered by the roadmap and to highlight the breadth and wide-ranging opportunities made available by FE technologies.
CRIS-Team Scopus Importer:2021-06-25
Keywords: E-textiles; Flexible and printed electronics; Organic light emitting diodes; Organic photovoltaics; Roll-to-roll printing; Sensors; Thin film transistors

Thin Film Encapsulation of Organic Solar Cells by Direct Deposition of Polysilazanes from Solution - Channa, Iftikhar Ahmed; Distler, Andreas; Zaiser, Michael; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2019)
Organic electronic devices (OEDs), e.g., organic solar cells, degrade quickly in the presence of ambient gases, such as water vapor and oxygen. Thus, in order to extend the lifetime of flexible OEDs, they have to be protected by encapsulation. A solution-based encapsulation method is developed, which allows the direct deposition of the diffusion barrier on top of OEDs, thus avoiding lamination of barrier films. The method is based on the deposition of a perhydropolysilazane (PHPS) ink and its subsequent conversion into a silica layer by deep UV irradiation. The resulting barrier films show water vapor transmission rates (WVTRs) of <10(-2) g m(-2) d(-1) (40 degrees C/85% relative humidity (RH)) and oxygen transmission rates (OTRs) of <10(-2) cm(3) m(-2) d(-1) bar(-1) at ambient conditions. Flexibility of the resulting barrier films is improved by coating a barrier stack of several thin PHPS layers alternating with organic polymer interlayers. These stacks show an increase of WVTR values by less than 10% after 3000 bending cycles. Direct coating of the PHPS films on top of organic solar cells enhances the device lifetime in damp heat conditions from a few hours to beyond 300 h.
CRIS-Team WoS Importer:2019-08-09

Upscaling of Perovskite Photovoltaics - Jang, Dongju; Yang, Fu; Dong, Lirong; Brabec, Christoph; Egelhaaf, Hans-Joachim (wiley, 2021)
Hybrid organic-inorganic perovskite solar cells have reached a certified efficiency of over 25% during the past decade, which has attracted significant attention as a promising candidate for photovoltaics (PVs) applications. However, the most efficient perovskite solar cells were performed by the spin coating technique, which is extremely limited in commercialization. Besides, the efficiencies of large-area perovskite cells and modules are still significantly lower. There are still some challenges that need to overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The most important challenge is how to prepare high-quality perovskite layers using cheaper and scalable techniques with high reproducibility. On the other hand, select and deposit charge extraction/transport layers, and the bottom and top electrodes using cheaper and scalable techniques are also important. In this review, recent progress and challenges of the scalable technologies for solution-based coating and printing methods are summarized and analyzed based on the current progress in scalable technologies for solution-based preparation of large-area perovskite PVs. Based on our analysis, we try to point out the major challenges to overcome to successfully bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. Finally, strategies and opportunities are proposed to promote stable and efficient large-area perovskite PVs toward commercialization.
CRIS-Team Scopus Importer:2024-12-16
Keywords: module; perovskite solar cells; roll-to-roll production; upscaling

Upscaling Solution-Processed Perovskite Photovoltaics - Yang, Fu; Jang, Dongju; Dong, Lirong; Qiu, Shudi; Distler, Andreas; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
The performance of hybrid organic–inorganic perovskite solar cells has reached a certified efficiency of 25.5% over the past decade, which has attracted significant attention as a promising candidate for photovoltaic (PV) applications. However, the most efficient perovskite solar cells were produced by the technique of spin coating, which is extremely limited in terms of upscaling production for the commercialization of the technology. Furthermore, the efficiencies of large-area perovskite modules are still significantly lower than those of lab size solar cells. Thus, there are still some challenges that need to be overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The first challenge lies in preparing high-quality perovskite layers by low-cost and scalable techniques with high reproducibility. Second, selecting and depositing charge extraction layers as well as bottom and top electrodes by scalable and low-cost techniques are essential tasks. In this review, recent progress and challenges of scalable technologies for solution-based coating and printing of perovskite PVs are summarized and analyzed. Based on the analysis, strategies and opportunities are proposed to promote the development of stable and efficient large-area perovskite PV toward commercialization.
CRIS-Team Scopus Importer:2021-10-22
Keywords: high-efficiency; long-term stability; perovskite photovoltaics; roll-to-roll production; scalable coating

Volatile Perovskite Precursor Ink Enables Window Printing of Phase-Pure FAPbI3 Perovskite Solar Cells and Modules in Ambient Atmosphere - Yuan, Linhao; Chen, Xining; Guo, Xianming; Huang, Shihao; Wu, Xiaoxiao; Shen, Yunxiu; Gu, Hao; Chen, Yujin; Zeng, Guixiang; Egelhaaf, Hans-Joachim; Brabec, Christoph; Yang, Fu; et al. (Angewandte Chemie International Edition, 2024)
Despite the great success of perovskite photovoltaics in terms of device efficiency and stability using laboratory-scale spin-coating methods, the demand for high-throughput and cost-effective solutions remains unresolved and rarely reported because of the complicated nature of perovskite crystallization. In this work, we propose a stable precursor ink design strategy to control the solvent volatilization and perovskite crystallization to enable the wide speed window printing (0.3 to 18.0 m/min) of phase-pure FAPbI3 perovskite solar cells (pero-SCs) in ambient atmosphere. The FAPbI3 perovskite precursor ink uses volatile acetonitrile (ACN) as the main solvent with DMF and DMSO as coordination additives is beneficial to improve the ink stability, inhibit the coffee rings, and the complicated intermediate FAPbI3 phases, delivering high-quality pin-hole free and phase-pure FAPbI3 perovskite films with large-scale uniformity. Ultimately, small-area FAPbI3 pero-SCs (0.062 cm2) and large-area modules (15.64 cm2) achieved remarkable efficiencies of 24.32 % and 21.90 %, respectively, whereas the PCE of the devices can be maintained at 23.76 % when the printing speed increases to 18.0 m/min. Specifically, the unencapsulated device exhibits superior operational stability with T90>1350 h. This work represents a step towards the scalable, cost-effective manufacturing of perovskite photovoltaics with both high performance and high throughput.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Large-Area Printing; Perovskite Solar Cells; Solar Module; Volatile Solvent; Wide Speed Window